Analysis of external load variables defining competitive demands in elite futsal through monitoring with tracking systems: a systematic review - Albalad-Aiguabella, R.; Mainer-Pardos, E.; Casajús, J. A.; Vicente-Rodríguez, G.; Muniz-Pardos, B. (Strength and Conditioning Journal, 2025)
The popularity of futsal is growing worldwide, leading to a greater professionalization of the sport and requiring coaches to have a deeper knowledge of its competitive demands. Advanced tracking systems allow for monitoring the physical demands associated with external load, which may aid coaches in understanding critical aspects to maximize sports performance. The present systematic review aims to identify the competitive demands of futsal in terms of external load measured via tracking systems. A search was conducted according to Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines in Web of Science, Scopus (Elsevier), and PubMed databases up to November 2023. Of the 318 citations, 12 met the inclusion criteria. High-intensity actions are important for futsal performance. The main external loading variables that assess efforts in elite futsal are total distance, distance covered per minute, high-intensity running, accelerations, and decelerations. It is essential to analyze the external load variables relative to time. In addition, and for a deeper understanding, the analysis of the physical demands should be further explored according to specific player positions (defenders, wingers, or pivots). Futsal performance seems to be determined by the player's ability to repeat multiple high-intensity actions in very short periods.